Incidence and characteristics of hypotensive transfusion reaction: 10‐year experience in a single center. Issue 11 (12th September 2022) - Kwon, Soon Sung; Kim, Sinyoung; Kim, Hyun Ok
Abstract: Background: Hypotensive transfusion reaction (HyTR) is rare. It is characterized by a rapid onset of hypotension during transfusion, which usually resolves quickly upon cessation of transfusion. Information on the incidence and clinical characteristics of HyTR has been reported in only a few studies. Study Design and Methods: We retrospectively reviewed HyTR cases from 10‐year hemovigilance data in a tertiary care hospital in Seoul, Korea. Results: We identified 37 HyTRs in 35 patients, and the overall incidence of HyTR was 0.50 per 10, 000 transfused units. Among the blood components, the incidence of HyTR was highest in filtered random donor platelets (0.75 per 10, 000 units). About half of the HyTRs occurred within 15 min after the start of transfusion (19/37). Blood pressure returned to the normal range within an hour in 73.0% of the cases (27/37). All HyTR cases recovered without severe complications. Known risk factors for HyTR were not prominent in our cohort of patients, with no patients taking angiotensin‐converting enzyme inhibitors and only five patients transfused with bedside filtered platelets. Discussion: HyTR can occur in patients with various conditions and types of blood components. Understanding the clinical characteristics of HyTR facilitates proper management, leading to improved transfusion safety.